The Usages of the Homage to the Five Supreme Entities in the Romance Poems (8th–12th Centuries) - Christine Chojnacki (Religions)
Used to mark devotion to the main propagators of Jainism, namely the Jina (arhat), the Liberated Souls (siddha), the Teachers (ācārya), the spiritual Guides (guru), the Preceptors (upādhyāya), and the monks (muṇi), the formula of homage to the five supreme entities (pañcanamaskāra) underwent a significant development in the medieval period where it became a mantra protecting against all evils and violence and symbolising Jainism in its entirety and its respect for life in all its forms amidst the various Indian religions. In the present paper, I intend to investigate how the formula was used in largely unknown romance poems composed in the Prakrit language by Jaina scholar monks in medieval North India between the 8th and 12th centuries. Particular attention will be paid to how the writer monks used the formula of homage in the narrative to avoid the use of violence. The analysis will also focus on the development of the formula in the hymns of praise of the romance poems and study its significance in the context of the spread of Jainism at the turn of the first millennium, a period that led to the advent of King Kumārapāla, who has remained famous in history not only for the imposing monuments he left behind, but also for his conversion to Jainism and his governance according to principles of non-violence.